Master's Programs in Patient Safety and Health Care Quality Worldwide. Issue 1 (January 2021) - Tekian, Ara; Infante, Alexander F.; Valenta, Annette L.
Abstract : Objectives: As we approach the 20th anniversary of the Institute of Medicine's report To Err Is Human: Building a Safer Health System, it is important to assess the progress we have made with respect to patient safety thus far. This study reviews all the existing master's-level degree programs worldwide and assesses them to determine trends and disagreements. Methods: Web-based searches were performed using phrases such as "masters, " "education, " "patient safety, " and "healthcare quality." Communication with programs representatives was used to obtain pertinent data not represented on the programs' webpages. Results: Twenty-five programs exist worldwide, 17 of which within North America. These programs are predominantly taught in a part-time format, with many providing an online setting for learning and requiring various forms of scholarship. Conclusions: Programs varied widely in credit hour structure and duration, as well as primary competencies. This highlights the need for the development of program standards to ensure the quality of such programs, as have been developed in other professional fields. Information pertaining to these programs including similarities, differences, trends, and characteristics is detailed in this section. The existence and development of these programs are paramount to future progression in health care, to prevent future errors by studying previous ones, thus improving health care.